Serotonin acts through multiple cellular targets during an olfactory critical period - Ahana Mallick; Hua Leonhard Tan; Jacob Michael Epstein; Clarissa Mei Jing Ng; Oliver Mason Cook; Quentin Gaudry; Andrew M. Dacks (iScience, 2024)
Summary: Serotonin (5-HT) modulates early development during critical periods when experience drives heightened levels of plasticity in neurons. Here, we investigate the cellular mechanisms by which 5-HT modulates critical period plasticity (CPP) in the olfactory system of Drosophila. We first demonstrate that 5-HT is necessary for experience-dependent structural plasticity in response to chronic CO2 exposure and can re-open the critical period long after it normally closes. Knocking down 5-HT7 receptors in a subset of GABAergic local interneurons was sufficient to block CPP, as was knocking down GABA receptors expressed by CO2-sensing olfactory sensory neurons (OSNs). Furthermore, direct modulation of OSNs via 5-HT2B receptors in CO2-sensing OSNs and autoreceptor expression by serotonergic neurons was also required for CPP. Thus, 5-HT targets individual neuron types in the olfactory system via distinct receptors to enable sensory driven plasticity.